Detecting Netizen Motives and Communication Psychology on Social Media - Lusi Noviani Prasetyo; Indra Gamayanto (Jurnal Audience: Jurnal Ilmu Komunikasi, 2023)
Social media has explicit and implicit information and is closely related to Sentiment analysis and Heuristic systematic models. These things will be the basic concepts that must be under before researching social media. However, problems such as comments and critics on social media, to this day, are still problems and may not have found the right solution to overcome these problems. Therefore, this research will answer these problems and provide solutions to overcome comments & critics. Before going any further, it should understand that this research is developing the journal Guidelines of Influencer Intelligence: Positive & Negative Impact of Influencers to Community. This research is systematic and structured, where concept after a concept developed, which will eventually produce a prototype and then an application. Still, we have to build a strong basic concept before going to the final stage. This research will produce complete profiling of comments & critics as a basic guide in knowing, understanding and deciding whether the comments & critics have quality, positive or negative impacts on society. The result of this article is a framework of comments & critics profiling, formulas and detailed explanations on the types of comments & critics so that they can be useful in making quality decisions for comments & critics.Keywords: Comment; Profiling; Social Media; Positive-Negative Impact; Wise Netizen